Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1042/bj3260069
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of mRNA for human epiregulin, a differentially expressed member of the epidermal growth factor family

Abstract: We have recently identified epiregulin as a new growth regulator and a member of the epidermal growth factor (EGF) family. Epiregulin has certain characteristics that are different from those of the classical members of the EGF family, EGF and transforming growth factor alpha, including mitogenic responses on several normal cells and binding to EGF receptors on epidermoid carcinoma A431 cells. In the present study we cloned and identified the expression of human epiregulin transcript. The human epiregulin gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
91
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 60 publications
(63 reference statements)
0
91
0
1
Order By: Relevance
“…High expression levels of the epiregulin gene have been shown in a number of cancer cell lines and activation of the Ki-Ras signaling pathway in colon cancer cells has been linked to the deregulation of epiregulin expression (Baba et al, 2000). Among the epidermal growth factor receptor ligands, epiregulin is distinguished by its more potent mitotic activity, the ability to bind various heterodimeric ErbB receptors (Shelly et al, 1998), and its unusual expression pattern, mainly in peripheral blood monocytes, macrophages and the placenta in normal human tissues, as well as in various types of epithelial tumor cell lines (Toyoda et al, 1997). In the mouse, epiregulin is expressed by tissue resident and peritoneal macrophages in vivo and its expression in macrophages is induced in response to the toll-like receptor agonists LPS and peptidoglycan in vitro (Shirasawa et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High expression levels of the epiregulin gene have been shown in a number of cancer cell lines and activation of the Ki-Ras signaling pathway in colon cancer cells has been linked to the deregulation of epiregulin expression (Baba et al, 2000). Among the epidermal growth factor receptor ligands, epiregulin is distinguished by its more potent mitotic activity, the ability to bind various heterodimeric ErbB receptors (Shelly et al, 1998), and its unusual expression pattern, mainly in peripheral blood monocytes, macrophages and the placenta in normal human tissues, as well as in various types of epithelial tumor cell lines (Toyoda et al, 1997). In the mouse, epiregulin is expressed by tissue resident and peritoneal macrophages in vivo and its expression in macrophages is induced in response to the toll-like receptor agonists LPS and peptidoglycan in vitro (Shirasawa et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…One of the candidate growth factors known to be critical in SCC development is epiregulin, a potent member of the epidermal growth factor family (Toyoda et al, 1997). We examined the epiregulin gene expression in the lungs of C57BL/6J mice during the course of infection with MTB using quantitative RT-PCR of total lung tissue.…”
Section: Chronic Mtb Infection Causes Squamous Cell Carcinomamentioning
confidence: 99%
“…In the intact animal, the expression of epiregulin transcript is detected during the early stages of embryonic life (Toyoda et al, 1995b). Furthermore, results from our laboratory have shown that the human epiregulin peptide deduced from cDNA sequence is highly homologous to mouse epiregulin and is biologically active (Toyoda et al, 1997). Although epiregulin inhibits the binding of [ 125 I]EGF to EGFR on A431 cells more weakly than EGF (Toyoda et al, 1995a), the direct binding of epiregulin to ErbB receptors has not been analysed.…”
Section: Introductionmentioning
confidence: 99%
“…EREG is proteolytically cleaved by a disintegrin and a metalloprotease 17 (ADAM17) to release soluble ligand that binds to and activates ERBB1/EGFR and ERBB4/Her4 (2,10,11). Expression of EREG in adults is restricted (12)(13)(14), but EREG is overexpressed in a number of human breast and colorectal cancer cell lines and tumors (15)(16)(17)(18)(19). EREG also has been implicated as a "metastasis driver" in breast cancer cells selected to metastasize to the lung (20).…”
mentioning
confidence: 99%